Effect of lithium on behavioral disinhibition induced by electrolytic lesion of the median raphe nucleus - Pezzato, Fernanda A.; Can, Adem; Hoshino, Katsumasa [UNESP]; Horta, Jose de Anchieta C. [UNESP]; Mijares, Miriam G.; Gould, Todd D. (Springer, 2015)
Alterations in brainstem circuits have been proposed as a possible mechanism underlying the etiology of mood disorders. Projections from the median raphe nucleus (MnR) modulate dopaminergic activity in the forebrain and are also part of a behavioral disinhibition/inhibition system that produces phenotypes resembling behavioral variations manifested during manic and depressive phases of bipolar disorder.The aim of this study is to assess the effect of chronic lithium treatment on behavioral disinhibition induced by MnR lesions.MnR electrolytic lesions were performed in C57BL/6J mice, with sham-operated and intact animals as control groups. Following recovery, mice were chronically treated with lithium (LiCl, added in chow) followed by behavioral testing.MnR lesion induced manic-like behavioral alterations including hyperactivity in the open field (OF), stereotyped circling, anxiolytic/risk taking in the elevated plus maze (EPM) and light/dark box (LDB) tests, and increased basal body temperature. Lithium was specifically effective in reducing OF hyperactivity and stereotypy but did not reverse (EPM) or had a nonspecific effect (LDB) on anxiety/risk-taking measures. Additionally, lithium decreased saccharin preference and prevented weight loss during single housing.Our data support electrolytic lesions of the MnR as an experimental model of a hyper-excitable/disinhibited phenotype consistent with some aspects of mania that are attenuated by the mood stabilizer lithium. Given lithium's relatively specific efficacy in treating mania, these data support the hypothesis that manic symptoms derive not only from the stimulation of excitatory systems but also from inactivation or decreased activity of inhibitory mechanisms.
Keywords: Bipolar disorder; Mania; Animal model; Lithium; Median raphe nucleus